IJCM_255A: Knowledge, attitude, and practice of No-Scalpel Vasectomy among married men attending a rural health facility in Kundrathur, Chennai - Karunya M; Kumar Thirumalai PR (Wolters Kluwer Medknow Publications, 2024)
Background: Male sterilisation, i.e., Vasectomy is one of the safest and most effective contraceptive methods as it has very low complication and failure rates. According to the NFHS-5 data, the male sterilisation rates in India and Tamil Nadu are about 0.3% and 0.1% respectively. Though there is sufficient knowledge on the effectiveness of No-scalpel vasectomy, there is lack of acceptance of male sterilisation as a permanent method of contraception Objective: To assess the knowledge, attitude and practice of No-scalpel Vasectomy among married men of Kundrathur, Chennai Methodology: A cross-sectional study was conducted among 116 married men between 22 to 60 years of age, attending the Upgraded Primary Health Centre, Kundrathur by consecutive sampling. A pretested semi-structured questionnaire was used to assess their knowledge and practice. Attitude was measured using 4-point Likerts scale. Data was analysed using SPSS software version 21 Results: Among the 112 participants who consented to participate in the study, 82 i.e., 73.2% of them were aware of vasectomy and the most common source of information was Mass media (51.2%). 74.2% agreed that contraception was not the sole responsibility of a wife, yet 48.2% of them disagreed that men should undergo vasectomy. The most perceived barrier for non-acceptance of vasectomy was Lack of awareness (33%), followed by Impotency following vasectomy (13.4%) and “Inability to do heavy work following vasectomy (12.5%). None of the participants (0%) underwent vasectomy, whereas 57.1% were willing to undergo, and 61.6% were willing to recommend the same to others. Conclusion: There seems to be a huge gap between the knowledge, attitude and practice of No-Scalpel Vasectomy among the study population. Thus, intense behavioural change communication should be advocated to increase the awareness and decrease the misconceptions regarding Vasectomy.